1997
DOI: 10.1111/j.1600-0897.1997.tb00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of IGF‐I and IGF‐II in Eutopic and Ectopic Endometria of Women With Endometriosis and in Women Without Endometriosis

Abstract: In endometriosis there is an alteration of mechanisms regulating cell proliferation and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 8 publications
1
12
0
2
Order By: Relevance
“…This is at variance with our study which showed that, while IGF-I was indeed decreased in endometriotic tissue, TGF b-1 was deexpressed. Also, an earlier study found that in eutopic endometria of women with endometriosis a reduction in IGF-I staining compared to normal was noted, whereas in the epithelial cells of fibrotic peritoneal adhesions an intense label for IGF-I was observed (Sbracia et al 1997). Another study demonstrated that IGF-I and IGF-II were present in both endometriotic and normal endometrium in equal amounts (Chang and Ho 1997).…”
Section: Discussionmentioning
confidence: 90%
“…This is at variance with our study which showed that, while IGF-I was indeed decreased in endometriotic tissue, TGF b-1 was deexpressed. Also, an earlier study found that in eutopic endometria of women with endometriosis a reduction in IGF-I staining compared to normal was noted, whereas in the epithelial cells of fibrotic peritoneal adhesions an intense label for IGF-I was observed (Sbracia et al 1997). Another study demonstrated that IGF-I and IGF-II were present in both endometriotic and normal endometrium in equal amounts (Chang and Ho 1997).…”
Section: Discussionmentioning
confidence: 90%
“…In comparison with endometrium, the integrin alpha 3 subunit was up-regulated; the alpha 6 integrin subunit was down-regulated, and the cycle stage-dependent expression of alpha 5 and beta 3 was absent in endometriosis [111]. The expression pattern of IGF-II and IGF-I was different in endometrium and endometriosis, suggesting an alteration in cell proliferation and differentiation in endometriosis [112]. The expression of plasminogen and plasmin was cycle dependent in endometrium, was maintained continuously at a high level in endometriosis [113], suggesting that this could reflect the more invasive nature of the endometriotic implants.…”
Section: Are Endometriotic Cells Different From Endometrial Cells or mentioning
confidence: 86%
“…Some of the proposed hypothesis include-Retrograde menses theory of Sampson, Coelomic metaplasia theory and Mullerian embryonic rest theory. [515] Dysregulation of a number of genes including aromatase, progesterone receptor and angiogenic factors has been shown in some studies. [16] Growth factors have also been implicated in pathogenesis of endometriosis by promoting endometrial proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%